2021
DOI: 10.1038/s41598-021-04039-4
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of the homodimers of HomA and HomB, outer membrane proteins of Helicobacter pylori

Abstract: Helicobacter pylori is a Gram-negative bacterium that causes chronic inflammations in the stomach area and is involved in ulcers, which can develop into gastric malignancies. H. pylori attaches and colonizes to the human epithelium using some of their outer membrane proteins (OMPs). HomB and HomA are the most studied OMPs from H. pylori as they play a crucial role in adherence, hyper biofilm formation, antibiotic resistance and are also associated with severe gastric malignancies. The role of HomA and HomB in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These data indicated that the protonated charge reversal ZAN@CS MNDs had a stronger antibacterial effect in acid environment compared with neutral conditions to ensure ZAN@CS MNDs could target to submucosa colonized H. pylori by electrostatic adsorption. [ 29 ] In addition, ZAN@CS MNDs were incubated in a simulated gastric mucosa and intestinal environment to visualize the morphology of ZAN@CS by TEM. As shown in Figure 2f, ZAN@CS MNDs degraded obviously at pH 4.2 with significant changes in morphology and size, and produced metal ions (Figure S6, Supporting Information), but no apparent morphological changes were observed at pH 7.4 (Figure 2g).…”
Section: Resultsmentioning
confidence: 99%
“…These data indicated that the protonated charge reversal ZAN@CS MNDs had a stronger antibacterial effect in acid environment compared with neutral conditions to ensure ZAN@CS MNDs could target to submucosa colonized H. pylori by electrostatic adsorption. [ 29 ] In addition, ZAN@CS MNDs were incubated in a simulated gastric mucosa and intestinal environment to visualize the morphology of ZAN@CS by TEM. As shown in Figure 2f, ZAN@CS MNDs degraded obviously at pH 4.2 with significant changes in morphology and size, and produced metal ions (Figure S6, Supporting Information), but no apparent morphological changes were observed at pH 7.4 (Figure 2g).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to other OMPs, recombination and phase variation are involved in gene duplication [37]. HomA/B are known for their significant roles in adherence, antibiotic resistance, biofilm formation and gastric malignancies [163]. Two important functions ascribed to HomB are IL-8 secretion and adherence [164].…”
Section: Hop V Hop W and Other Ompsmentioning
confidence: 99%
“…H. pylori has more than 60 OMPs coding genes [ 46 ], but not all the OMP’s functions are understood [ 40 ]. Beyond inducing the pro-inflammatory responses, some OMPs were also found to promote multiple processes of H. pylori biofilm formation, one of which is to promote surface adhesion as discussed [ 47 , 48 ]. H. pylori OMPs facilitate both cell-to-cell and cell-to-abiotic surface adhesion in biofilms, based on the observation of OMV localization in H. pylori biofilms via scanning electron microscopy (SEM) imaging [ 49 ].…”
Section: Adherencementioning
confidence: 99%
“…HomA and HomB are composed mainly of β-sheets with cysteine resides on surface loops that help to form homodimers and indicate that they are potentially key to aggregation and biofilm formation [ 48 ]. Various studies demonstrated that HomB is negatively regulated by a two-component system, ArsRS system [ 19 , 25 , 50 ].…”
Section: Adherencementioning
confidence: 99%